(untitled) (Colloquia Comparativa Litterarum, 2025)
Interlitteraria. Vol. 21, No 1 (2016). Belletristic Translation: a Means of Cultural-Spiritual Dialogue or a Tool of Acculturation?; Miscellanea. University of Tartu Press, Eesti/Estonia, 2016.